Efficient Organic Solar Cells with a High Open‐Circuit Voltage of 1.34 V. Issue 11 (14th October 2019) - Gao, Bowei; Yao, Huifeng; Hong, Ling; Hou, Jianhui
Summary of main observation and conclusion: One of the most important challenges that hinders the power conversion efficiencies (PCEs) of organic solar cells (OSCs) is the modest open‐circuit voltages ( V OC ) due to large energy losses. The large driving force during for charge generation and the non‐radiative recombination are the main causes of energy losses. To maximize the V OC of OSCs, herein, we modulate the end‐groups and design a non‐fullerene acceptor ITCCM‐O, which shows a bandgap of 2.0 eV. By blending a polymer donor named J52, the device demonstrates a PCE of 5.5% with an outstanding V OC of 1.34 V, which is the highest value for single‐junction OSCs over 5% PCEs. The high V OC is benefited from 1) the negligible driving force for charge transfer, and 2) the suppressed non‐radiative recombination loss, as low as 0.22 V. Abstract : We synthesized a new wide bandgap non‐fullerene acceptor ITCCM‐O. By blending with a polymer donor J52, the photovoltaic cell achieved an impressive V OC of 1.34 V.